Grain size softening effect in intermetallics - Basariya M.R.; Mukhopadhyay N.K.; Sripathi S.; Padmanabhan K.A. (My University, 2025)
Inverse Hall–Petch/grain size softening effect is a phenomenon, which when present, leads to a decrease in flow stress with a decrease in grain size. The manifestation of this phenomenon at room temperature in nanostructured intermetallics, including some of our new results, is discussed here. Following earlier work, the IHP effect is attributed to the loss of intra-crystalline dislocation motion control to mesoscopic (≥a grain diameter) grain/interphase boundary sliding controlled flow, which evidently is confined to the grain/interphase boundary regions. Equations for estimating the free energy of activation (same as the activation energy) for the rate controlling process, the free volume fraction present in a basic sliding unit and the average number of grain boundaries that align to form a plane interface during superplastic deformation, derived in earlier papers, are used to account for this phenomenon quantitatively in the present case also. © 2016 Elsevier B.V.